PENGEMBANGAN PRODUK MINUMAN ISOTONIK ALAMI BERBASIS EKSTRAK TEPUNG PISANG KEPOK KUNING (MUSA PARADISIACA FORMAL TYPICAL) DAN PENGARUHNYA TERHADAP REHIDRASI - , Mirza Hapsari Sakti Titis Penggalih, Prof. Dr. Ir. Murdjati Gardjito ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. Hot temperatures increase the risk of dehydration. Isotonic beverage has been developed to prevent it but not with a natural material. Banana is a fruit that contains carbohydrates and electrolyte. Fluid can prevent dehydration. It should contain electrolytes with certain osmolarity. Banana isotonic drinks (BID) was developed and the study of it efficacy need to be evaluated. Objective. This research aims to create formulation of isotonic drink based on banana flour extraction. This study aims was also to determine the difference effect of BID and plain water (PW) of body hydration Methods. The first stage for the product development was an experimental research that includes the creation of flour, carbohydrate and electrolyte analysis, and osmolarity test of formulation drinks. The second stage was an experimental research to test the effect of rehydration with cross-over design involving 16 subjects who were divided into 2 groups. Subjects quarantined for 2 days and then given fluids of 500 ml plain water (PW) and Banana isotonic Drink (BID) with a wash-out period was 7 days between trial. Indicators of heart rate, blood pressure, mean arterial pressure (MAP), pulse pressure, body weight (BW), hemoglobin (Hb), hematocrit (HCT), blood volume and urin were assesd before, after treatment and after 2 h rehydration. Results. These drinks has succeeded develop with the basic materials of 105 days old of banana flour extraction. Each 100 ml waters contain of 24% banana flour, salt and sugar in small amounts. The drink is making simply by dissolving the material into cold water. The result showed that indicator of hydration differed significantly after receiving the intervention (P<0.05) on urine volume, heart rate, diastolic, upright systolic, and MAP. There were significant different between group in systolic pressure (P<0.05). Conclusion. BID is able to improve the hydration of the body through the mechanism of maintaining body volume and slowing down the urine formation.